Interaction of obtusilactone B and related butanolide lactones with the barrier-to-autointegration factor 1 (BAF1). A computational study - Christian Bailly; Gérard Vergoten (Elsevier, 2021)
The barrier-to-autointegration factor 1 (BAF1) protein is a DNA-binding protein implicated in nuclear envelop repair and reformation after mitosis. This nuclear protein is frequently overexpressed in cancer cells and plays a role in the occurrence and development of different tumors. It is a potential therapeutic target for gastric cancer, breast cancer and other malignancies. For this reason, BAF1 inhibitors are searched. The butanolide lactone obtusilactone B (Ob-B) has been found to inhibit VRK1-dependent phosphorylation of BAF1, upon direct binding to the nuclear protein. Taking advantage of the known crystallographic structure of BAF1, we have elaborated molecular models of Ob-B bound to BAF1 to delimit the binding site and binding configuration. The long endoolefinic alkyl side chain of Ob-B extends into a small groove on the protein surface, and the adjacent exomethylene-γ-lactone moiety occupies a pocket comprising to the Ser-4 phosphorylation site of BAF1. Twenty butanolide lactones structurally close to ObB were screened for BAF1 binding. Several natural products with BAF1-binding capacity potentially superior to Ob-B were identified, including mahubanolide, kotomolide B, epilitsenolide D2, and a few other known anticancer plant natural products. Our study provides new ideas to guide the discovery and design of BAF1 inhibitors.